Molecular Detection of Colistin Resistant Gene mcr-1 from Gram Negative Clinical Isolates - Devkota, Asmita; Shah, Anil Kumar; Thapaliya, Srijana (SXC Journal, 2025)
Colistin is the last resort antibiotic for treating carbapenem-resistant Gram-negative bacterial infections. The emergence of plasmid-mediated mobile colistin-resistant (mcr) genes in Enterobacteriaceae has raised concern due to the possibility of rapid horizontal spread. The global dissemination of mobile colistin-resistant genes in natural and non-natural environments is a major problem in the fight against antimicrobial resistance. This study aimed to determine the prevalence of the mobile colistin-resistant gene mcr-1 in Gram-negative bacteria obtained from different clinical specimens. 753 clinical samples were collected from patients visiting Annapurna Neurological Institute and Allied Sciences, Maitighar (January 2019 to July 2019). Clinical specimens were cultured and identified using biochemical tests. Antibiotic Susceptibility Testing (AST) was done by the modified Kirby Bauer disc diffusion method using a colistin disc (10μg), colistin resistance was confirmed by using the E-test. In this study, 180 (23.90%) isolates showed growth, among which the identified bacteria were E. coli, Klebsiella spp., Citrobacter spp., Acinetobacter spp. and Pseudomonas spp. Colistin resistance was higher in male patients (12.35%) than in female patients (7.69%) and higher in the age group between 21-40 years. AST revealed, 79.44% of isolates were multidrug resistant (MDR) and colistin showed 90% sensitivity towards Gram-negative bacteria. The highest resistance was demonstrated against Cotrimoxazole, 65.26%. Similarly, the highest percentage of colistin resistance was observed in urine samples (14.49%), among isolates from the ICU ward (16.66%) and in E. coli (16.07%). Out of the total of 180 isolates, 11.66% were screened as colistin resistant, while E-test confirmed 10% isolates phenotypically. The mcr-1 genes were detected only in 33.33% of E-test confirmed samples using PCR assays and gel electrophoresis. Early detection of these gene-related infections is of great importance to monitor and control the spread of antibiotic resistance.